The Development and Psychometric Testing on Psychiatric Nurses of a Nurse Case Management Competence Scale in Taiwan. Issue 2 (April 2018) - Chen, Shing-Chia; Lee, Shih-Kai; Rong, Jiin-Ru; Wu, Chien-Chang; Liu, Wen-I
ABSTRACT: Background: Case management is a complex process involving multiple activities. It is vital that nurses are competent in all related tasks for case management. A competence scale is a valuable tool for assessing task-related competency. Purpose: The aims of this study were to examine the reliability and validity of an assessment scale for nurse case management competence and to use this scale to assess the current competency of nurses. Methods: A nurse case management competence scale was developed in three stages: (a) selection of assessment items according to standards of practice for case management and literature review, (b) determination of content validity using the Delphi technique with a panel of experts, and (c) psychometric testing of the developed competence scale using a cross-sectional design. Convenience sampling was used to recruit psychiatric nurses at seven psychiatric centers in Taiwan to complete the scale anonymously. An exploratory factor analysis was performed to analyze construct validity. Discriminant validity, internal consistency, and 2-week test–retest reliability were also examined. Results: Two hundred eighty-five psychiatric nurses completed an assessment scale comprising 18 items (originally 25 items). The content validity index reached 0.96 after the Delphi technique was applied twice in the expert panel. Seventy-eight percent of the total variance was explained by two dimension factors: coordination facilitation competence and direct care competence. Participants who had undertaken case management courses had superior case management ability compared with those who had not, indicating that the scale possesses excellent discriminant validity. Cronbach's α and the test–retest results showed excellent reliability. Of the two competence factors, direct care competence (3.03) was better than coordination facilitation competence (2.81). Conclusions/Implications for Practice: There is a dearth of studies investigating the development and psychometric testing of case management competence scales. The results of this study provide evidence to support the reliability and validity of the developed case management competence scale among Taiwanese psychiatric nurses. It is a reliable and valid assessment instrument that may help identify educational needs and improve the case management competencies of nurses.